Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Tingkat Retensi Karyawan di Industri Jasa - Elok Cahyaning Pratiwi; Mila Hariani (Journal of Trends Economics and Accounting Research, 2023)
High levels of work motivation and supportive work environment conditions are considered key factors for retaining employees in an organization. The purpose of this study is to analyze the impact of the factors of work motivation level and work environment conditions on the retention rate of workers in the service industry. A quantitative approach was used in this study, with data analysis using multiple linear regression. The study sample consisted of 83 employees in the service industry in Surabaya City who were selected through a saturated sampling approach. Regression analysis was used to examine the relationship between employee retention levels with work environment and work motivation. Regression analysis was used to analyze the impact of the factors of work motivation level and conditions in the work environment with the level of employee retention. This study indicates that there is a real (significant) impact on work motivation and work environment on the level of employee retention in the service industry in Surabaya City.